The role of women in driving national innovation and entrepreneurship through entrepreneurial ecosystems - Naeimah Alkharafi (Journal of Innovation & Knowledge (JIK), 2024)
Entrepreneurial ecosystems create a conductive environment for innovation and advancing sustainable development. They stimulate national innovation and economic development; however, empirical examination, especially in emerging economies, remains limited. Using longitudinal data on 89 countries for 2018-2021, this study empirically tests three pillars of entrepreneurial ecosystems - resource supply, resource demand, and allocation and accumulation - through a gendered lens to explore their effect on national innovation and entrepreneurship. We estimate regional effects with a three-dimensional fixed effects regression model. Our results suggest that knowledge capital of female researchers and domestic economy size are the central drivers of national innovation and entrepreneurship, respectively. Furthermore, this effect is more critical for emerging economies and disappears as countries develop. We present a gendered empirical examination of Audretsch et al.'s (2022) framework and elucidate the contributions of women in driving national innovation through ecosystems in emerging economies.
Keywords: J16; J18; O11; O19; O30; O57; 650; Entrepreneurial ecosystem; Innovation; Entrepreneurship; Gender; Sustainable economic development